Inventions : a visual encyclopedia - Farndon, John (DK Publishing, 2018)
Provides encyclopedic entries highlighting notable inventions throughout human history. Each entry is placed in a specific category such as early breakthroughs, transportation, industrialization, communication, and medicine, and has basic statistics of who, what, where, and when, and a brief description of why the entry is notable. Includes color illustrations and photographs, a reference section listing famous inventors, a glossary, and an index.